Housing and the macroeconomy: The role of implicit guarantees for government-sponsored enterprises - Karsten Jeske; Dirk Krueger (Federal Reserve Bank of Atlanta, 2005)
This paper studies the macroeconomic effects of implicit government guarantees of the obligations of government-sponsored enterprises. We construct a model with competitive housing and mortgage markets in which the government provides banks with insurance against aggregate shocks to mortgage default risk. We use this model to evaluate aggregate and distributional impacts of this government subsidy of owner-occupied housing. Preliminary findings indicate that the subsidy leads to higher equilibrium housing investment, higher mortgage default rates, and lower welfare. The welfare effects of this policy vary substantially across members of the population with different economic characteristics.
Keywords: E21; G11; R21; 330; housing; mortgage market; default risk; Hypothek; Hypothekenbank; Öffentliche Bank; Kreditrisiko; USA; Makroökonomischer Einfluss